Crypto currency and Shariah compliant aspects: an overview - Md Nor, Mohd Zakhiri; Iskandar Mirza, Azrul Azlan; Bakri, Mohammed Hariri; Abdul Aziz, Nor Azah; Md Razak, Mohamad Idham; Abdul Hamid, Mohd Hakim; Zainal, Nurshuhada; Zaharin, Hussaini (Association Res Militaris, 2022)
Many countries have seen growth in the use of crypto currency. However, it was not widely recognized as a legal tender or currency and Shariah scholars have different views on the permissibility of crypto currencies. The main problem is unclear which Islamic commercial contracts should be applied in crypto currency and block chain technology. This research's primary goal is to investigate contemporary Shariah scholar’s opinion and fatwa on this area. In this study, the qualitative research method was applied. The information will be obtained through library research. The content analysis method was used to analyses this data. This study found that, while bit coin is not entirely legal tender in Malaysia, it is a digital asset that must closely adhere to the Shariah Resolution issued by the Malaysian Securities Commission.